THE SCIENTIFIC VIEWPOINT IN STATE ISLAMIC UNIVERSITY IN INDONESIA - Toto Suharto; Khuriyah Khuriyah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2014)
This paper aims to reveal that this family of general (secular) scientific and religious scientific can be integrated into such a view of the epistemology of science as applied institute non-dichotomous state Islamic University or UIN. Basically is Law No. 12 in 2012 and the decision of the Director General of Islamic Education No. 3389 Year 2013 The method used is content analysis approach to the study of philosophy and Islamic education policy. The analysis showed that the Islamic colleges that have shaped the university can be in organizing educational and scientific development of both general and religious clumps. This is called the integration and interconnection (non-dichotomous) scholarly knowledge of Islam among the general sciences. Scientific form of integration is reflected in the naming of the faculty (eg. Tarbiyah and Teaching Science, Adab and Humanities, Faculty of Da'wa and Communication) and the distribution of subjects. In essence, in each course served at UIN containing core Islamic sciences, both normative and descriptive.